Implementation of Character Education in the Learning Process of Hindu Religious Education in Elementary Schools - Kiriana, I Nyoman; Okta Priantini, Dewa Ayu Manu (International Journal of Elementary Education, 2021)
The problem behind this research is the lack of inculcation of character values among students. This study aims to analyze the implementation of character education in the learning process of Hindu religious education. This type of research is qualitative using a qualitative descriptive approach. The subjects in this study were elementary school teachers and students. Data collection techniques used in this study are observation, interviews and documentation. The data analysis method used is in the form of qualitative descriptive analysis, namely the process of systematically searching and compiling data obtained from interviews, field notes, and documentation, by organizing data into categories, breaking down into units, synthesizing, compiling into patterns, choosing which ones are important, and which will be studied, and making conclusions so that they are easily understood by themselves and others. Based on the results of the research and discussion that have been described, it can be concluded that the implementation of character education is only able to find 14-character values. The character values studied consist of 18-character values in the development of cultural and national character education by the Ministry of Education and Culture so that it can be concluded that the cultivation of character values has been carried out very well, although it is still maximal.